(untitled) (Global Journal of Human-Social Science, 2024)
The study of the consistency of the principe of transparency and good governance in cameroonian budgetary law involves treatig the content of the said principle in the normative field which governs budgetary engineering It emerges that the principle of transparency and good governance in budgetary law consists of a liberalization of management public budgetary Indeed this principle present itself as information to the public on the public budget management This reality truly emerges from then on that this information in exercised on all past present and future budgetary and extrabudgetary activities of the budgetary management of public entities on the one hand and that thisinformation of the public is presented as obligatory regular and exhaustive on the other hand Likewise the principle of transparency and good governance in cameroonian budgetary matters also consists of control of public budgetary management This control itself relating firstly to administrative control with multiple forms multiple procedures and the nature diversify and secondly to a control of the national representation alongside which stands the audit chamber of the supreme court Anything that aims at the construction of sustainable democratic budgetary management